2011
DOI: 10.2298/bah1104585k
|View full text |Cite
|
Sign up to set email alerts
|

Yield and quality of winter common vetch (Vicia sativa L.) haylage depending on sowing method

Abstract: In order to determine an optimum ratio of vetch and wheat (Triticum aestivum L.) components in their mixture, there has been carried out a four-year trial (autumn 2005-spring 2009) aimed at the yield and quality of winter vetch haylage. The sowing rate of winter vetch was 120 kg ha-1 , while the sowing rate of winter wheat was 0, 15, 20, 25 and 30 kg ha-1. An increased proportion of the cereal in its mixture with vetch significantly decreases the stand lodging, have a positive influence on forage yield, but ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 16 publications
7
13
0
Order By: Relevance
“…In this study pure legume plant had lower ADF content than annual ryegrass and annual ryegrass mixtures with legume. ADF concentrations decreased as the legume proportion increased in the mixtures and similar results have also been reported by Karagic et al (2011); Sadeghpour et al (2014); Kusvuran et al (2014).…”
Section: Adf (%)supporting
confidence: 87%
See 2 more Smart Citations
“…In this study pure legume plant had lower ADF content than annual ryegrass and annual ryegrass mixtures with legume. ADF concentrations decreased as the legume proportion increased in the mixtures and similar results have also been reported by Karagic et al (2011); Sadeghpour et al (2014); Kusvuran et al (2014).…”
Section: Adf (%)supporting
confidence: 87%
“…Pure Lolium multiflorum stands produced herbage with the lowest crude protein content. When the ratio of legume plant in the mixture increased, so did the crude protein content of that mixture also, and on the contrary as proportion of the grass increased in the mixture crude protein content significantly decreases (Karagic et al, 2011). The mean crude protein content for grass + legume mixtures observed in this study were found to be similar with the results of Lithourgidis et al (2007); Kramany et al (2012) and Kusvuran et al (2014).…”
Section: Crude Protein Content (%)supporting
confidence: 84%
See 1 more Smart Citation
“…Intercropping of cereallegume species is also widespread due to its advantages for soil conservation (Anil et al, 1998), weed control, lodging resistance (Karagic et al, 2011), higher yield, and increased fodder quality (Lithourgidis et al, 2006). Different small grain cereals and vetches have been successfully used in cereal-legume intercropping systems (Dhima et al, 2007;Karagic et al, 2011;Lithourgidis et al, 2011).Since a greater proportion of dry matter produced by barley during blooming and inflorescence is digestible and nutritious, barley is considered a superior quality forage crop compared to other cereals (Carr et al, 2004). Common vetch is a popular legume used for fresh and dry fodder and silage production in Turkey.…”
mentioning
confidence: 99%
“…Crude protein yield of forage is one of the main criteria for forage quality. In all mixtures, an increase in the rate of vetch resulted in higher crude protein yield (Karagic et al, 2011). This was expected since legume establishment was greatly enhanced by the barley support, resulting in a higher protein-rich legume proportion in the mixture.…”
Section: Crude Protein Yield (Cpy)mentioning
confidence: 84%